Mites (Mesostigmata: Melicharidae) associated with hummingbirds (Aves: Trochilidae) in Brazil - Bassini-Silva, R. [UNESP]; Takatsu, J. C.; Peinado, L. C.; Faxina, C.; Moreira-Lima, L.; Fischer, E.; Hingst-Zaher, E.; Santos, J. C.; Moraes, G. J.; Dowling, A. P.G.; Barros-Battesti, D. M. [UNESP]; Jacinavicius, F. C. (Taylor & Francis, 2021)
Mites of the family Melicharidae comprise 13 genera and 220 species often associated with edaphic environments and found in association with insects, birds and mammals. Two genera, Proctolaelaps and Tropicoseius, have been recorded in Brazil in association with birds and bromeliads. In this study, we add new locality and host-association records for Proctolaelaps superagui and Tropicoseius braziliensis in the country.
Keywords: Brazil; Melicharid mites; Neotropical region; phoresy; Trochilidae